2023
DOI: 10.3390/nano13081434
|View full text |Cite
|
Sign up to set email alerts
|

The Hydrogenation of Crotonaldehyde on PdCu Single Atom Alloy Catalysts

Abstract: Recyclable PdCu single atom alloys supported on Al2O3 were applied to the selective hydrogenation of crotonaldehyde to elucidate the minimum number of Pd atoms required to facilitate the sustainable transformation of an α,β-unsaturated carbonyl molecule. It was found that, by diluting the Pd content of the alloy, the reaction activity of Cu nanoparticles can be accelerated, enabling more time for the cascade conversion of butanal to butanol. In addition, a significant increase in the conversion rate was observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Generally, in the case of reduced Cu nanowires or nanoparticles, their color turns to dark gray after the introduction of precious metal salts, suggesting the replacement of Cu by Pt or Pd during the GR reaction and formation of CuPt and/or CuPd SAAs. 51 In terms of reaction media, besides dilute water, dimethyl sulfoxide has been used as a polar aprotic solvent to prevent some host particles from agglomerating in distilled water. 50 However, Mohl et al found that Pt and Pd ions tended to aggregated to form the corresponding nanoparticles in ethanol solvent.…”
Section: Methods For the Preparation Of Saa Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, in the case of reduced Cu nanowires or nanoparticles, their color turns to dark gray after the introduction of precious metal salts, suggesting the replacement of Cu by Pt or Pd during the GR reaction and formation of CuPt and/or CuPd SAAs. 51 In terms of reaction media, besides dilute water, dimethyl sulfoxide has been used as a polar aprotic solvent to prevent some host particles from agglomerating in distilled water. 50 However, Mohl et al found that Pt and Pd ions tended to aggregated to form the corresponding nanoparticles in ethanol solvent.…”
Section: Methods For the Preparation Of Saa Catalystsmentioning
confidence: 99%
“…Zhang et al prepared the 0.1Pt–Cu/SiO 2 SAA, where Pt was isolated as single atoms and formed the Pt–Cu alloy phase. 65 They found that only 0.1 wt% isolated Pt with the surrounding Cu atoms improved the dispersion of Cu, increased the Cu + /Cu 0 ratio and enhanced hydrogen activation without causing the C–C cleavage side reaction. Consequently, PtCu-SAA catalysts afford a reduced reaction temperature, unique ethanol selectivity as high as 76.7% and promising stability of over a 700 h time on stream in the methyl glycolate reaction.…”
Section: Applications Of Saa Catalystsmentioning
confidence: 99%
“…In this context, this Special Issue compiled 11 high-quality contributions [6][7][8][9][10][11][12][13][14][15][16] (10 collected from PSC participants and 1 from others), covering recent research progress in the titled theme. These articles are briefly discussed below.…”
Section: General Remarksmentioning
confidence: 99%
“…The selective hydrogenation of crotonaldehyde was studied by Kyriakou and coworkers [13] on recyclable PdCu single atom alloys supported on Al 2 O 3 to elucidate the minimum number of Pd atoms required to facilitate the sustainable transformation of an α,β-unsaturated carbonyl molecule. By diluting the Pd content of the alloy, the reaction activity of Cu nanoparticles can be accelerated, enabling more time for the cascade conversion of butanal to butanol.…”
Section: Contributions and Highlights Of This Special Issuementioning
confidence: 99%